2022
DOI: 10.3390/ma15030868
|View full text |Cite
|
Sign up to set email alerts
|

Corn Cob Ash versus Sunflower Stalk Ash, Two Sustainable Raw Materials in an Analysis of Their Effects on the Concrete Properties

Abstract: The increased CO2 emissions determined by the cement industry led to continuous and intensive research on the discovery of sustainable raw materials with cementitious properties. One such raw material category is agricultural waste. This study involved research on the effects of corn cob ash and sunflower stalk ash, respectively, on compressive strength measured after 28 days and 3 months, the flexural and splitting tensile strengths, the resistance to repeated freeze–thaw cycles, and on the resistance to chem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 22 publications
0
6
0
1
Order By: Relevance
“…In this matrix, the number of targets achieved per goal was identified and then divided by the total number of targets for the same goal. References [67][68][69] are cited in the supplementary materials.…”
Section: Supplementary Materialsmentioning
confidence: 99%
“…In this matrix, the number of targets achieved per goal was identified and then divided by the total number of targets for the same goal. References [67][68][69] are cited in the supplementary materials.…”
Section: Supplementary Materialsmentioning
confidence: 99%
“…Several investigations have been attempted by a number of researchers to develop alternative cementitious materials using HRA. Rice husk ash (RHA) [ 5 ], palm oil fuel ash (POFA) [ 6 ], sugar cane bagasse ash (SCBA) [ 7 ], wheat straw ash (WSA) [ 8 ] and corn cob ash (CCA) [ 9 ] are some of the HRA that have evidently been reported for their suitability as pozzolans. The majority of the agricultural biomass resources in Serbia lie in corn biomass, more than 25% in the straw of cereals, and the rest in harvest residues of sunflower, soybean and oilseed rape.…”
Section: Introductionmentioning
confidence: 99%
“…Few earlier studies are available on the effect of WSA incorporation on the flexural and compressive strength of blended cement mortar [ 11 ] and masonry mortar [ 8 ]. No studies referring to CCA application in cement-based composites in Serbia can be found, while there have been studies giving an account of this by-product utilization as a SCM in other countries [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…(19) Añadir ceniza de cáscara de arroz en el concreto autocompactante aumenta la resistencia a la comprensión hasta un 15 % de valor de reposición (7) y la combinación porcentual de ceniza de maíz y ceniza de tallo de girasol aumenta hasta un 10 % para obtener una mayor ganancia de resistencia. (20) El principal objetivo de esta investigación es evaluar la sustitución del cemento por ceniza de cáscara de arroz y ceniza de paja de ichu, en porcentajes de 2 %, 4 % y 6 % y determinar su influencia en las propiedades en estado fresco y la resistencia a la comprensión del concreto autocompactante considerando testigos de concreto a distintas edades de curado.…”
Section: Introductionunclassified